Human embryology and developmental biology - Carlson, Bruce M.
Master the concepts you need to know with Human Embryology and Developmental Biology. Dr. Bruce M. Carlson's clear explanations provide an easy-to-follow "road map" through the most up-to-date scientific knowledge, giving you a deeper understanding of the key information you need to know for your courses, exams, and ultimately clinical practice